Integrating Go-To-Market Strategies with GenAI for Successful Product Launches (International Journal of Information and Electronics Engineering, 2023)
This work aims to establish how Go-To-Market (GTM) frameworks can leverage “Generative Artificial Intelligence” (GenAI) to achieve effective product launches. Through using tools such as GPT and DALL-E, the marketing content can be enriched, the range of customers determined, and the potential of predictive analysis increased dramatically, which in turn will contribute to the increase of ROI and customer satisfaction.